Keynes, the Keynesians and Monetarism - Tim Congdon (Edward Elgar Publishing, 2007)
Keynes, the Keynesians and Monetarism is a major contribution to the continuing debate on macroeconomic policy-making. Tim Congdon has been a strong supporter of monetarist economic principles for over 30 years. His writings - in the newspapers and for parliamentary committees, as well as in academic journals - played an influential role in the transformation of British macroeconomic policy in the 1980s and 1990s. This book brings together the main papers written by the author since his 1992 collection, Reflections on Monetarism. It challenges several 'conventional wisdoms' about UK macroeconomic policy (and thinking about policy), arguing - for example - that the Keynesians' advocacy of incomes policy and fiscal activism in the immediate post-war decades did not have a clear basis in Keynes's own writings. The book denies that the UK had a 'Keynesian revolution', in the sense of a deliberately pursued fiscal activism to promote 'full employment'. Implicit throughout the volume is a distinctive view of how the economy works, with an account of the transmission mechanism (from money to the economy) in which movements in asset prices and aggregate demand are strongly influenced by the quantity of money. Congdon uses this approach to demonstrate that monetary policy has had more powerful effects on macroeconomic activity in the post-war period than fiscal policy. He also suggests that the now fashionable 'New Keynesian' view of policy-making acknowledges the primacy of monetary policy and would be better termed 'output gap monetarism'. In short, Keynes, the Keynesians and Monetarism contends that monetarism defeated Keynesianism in the battle of ideas in the 1970s and 1980s. The achievement of greater macroeconomic stability in the last 15 years is largely due to the impact of monetarist thinking on policy-making. The book is clearly and attractively written, and covers topics that are fundamental to macroeconomic thinking and policy-making. It will be a provocative and appealing read for scholars at all levels of economics, macroeconomics and monetary theory. It will also find an audience among policymakers in central banks and finance ministries, business economists working in companies, and financial economists in the City of London and other centres.